Erisudar - Nagayah, Sunder (Nanyang Technological University, 2022)
Erisudar is a film that pits predeterminism against free-will. The constant battle between these 2 concepts is a lifelong experience for the conscious mind, which yields no peaceful conclusion. The film explores one such instance in the life of a man whose sole purpose has been to examine the extent to which our lives are predetermined. He is visited by a teenage girl, who is seeking to find answers of her own. In the few moments with her, the astrologer's grip on his own reality fluctuates, leading to a key moment where his principles are on the line, and he is forced to make a decision. Erisudar is an investigation of how much control we have over our lives.